MERAJUT SINERGI PGSD DAN PAI: STRATEGI MEMBANGUN PROFIL PELAJAR PANCASILA YANG BERAKHLAK MULIA DAN BERKEBINEKAAN GLOBAL DI SD - Merliana Putri Manafe; Diaz Astiza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe and formulate a synergy strategy between Elementary School Teacher Education (PGSD) and Islamic Religious Education (PAI) in shaping the Pancasila Student Profile, especially in the dimensions of Noble Morals and Global Diversity in elementary schools. This research uses a descriptive qualitative approach through library research. Data was obtained from secondary sources such as books, accredited national journals, government documents, and other relevant scientific publications. Data analysis used content analysis to identify and synthesize concepts from various sources. The research results show that synergy can be realized through; (1) integrated learning planning with a deep learning approach and co-planning between teachers; (2) implementation of learning through team teaching, project-based learning (P5), and habituation of school culture; and (3) holistic and collaborative evaluation. The implication of this synergy enriches holistic and interdisciplinary learning literature and provides practical guidance for schools, teachers, and LPTK. The main challenges include curriculum integration, teacher readiness, and limited collaboration time, which require solutions such as active learning, differentiated learning, digital literacy training, and strong commitment from school leaders.